Design and development of energy management system for household users - Thng, Joell Chong Shu (Nanyang Technological University, 2020)
This report focuses on Demand Side Management application in the residential sector in Singapore. New houses are being built every year, increasing the demand of electricity. Although the increase in demand of electricity is inevitable, Demand Side Management can reduce the amount of energy being consumed. One application of Demand Side Management is Demand Response techniques. Demand Response is an analysis technique for electrical consumption. Home Energy Management System is a controller tool which helps household users analyse patterns in their energy usage.